Analysis Comparative of Internet Service Providers on Upload andDownload Speeds - Ika Mirad Saputri; Aida Dahnia Nur; Aviva Inggita Delsa; Husen M. Hasan Amir (Universitas Islam Al-Azhar Mataram, 2024)
In today's growing digital era, the internet has become one of the main bases infulfilling people's needs ranging from work, education, even for entertainment aloneis now very dependent on a fast and stable internet connection. The development ofcurrent network technologies such as Fiber Optic, 5G has provided an increase ininternet capacity and speed for each Wi-Fi provider. The purpose of this study is todetermine the comparison between several Wi-Fi providers commonly used inmeeting communication and connectivity needs. This article aims to conduct acomparison between several Wi-Fi providers, based on 3 main factors namely, speed,coverage, and signal quality. This analysis is used to evaluate the performance ofeach provider in each of these factors. Through field data collection, speed tests, usersurveys. This article provides an insight into the strengths and weaknesses of eachprovider. The results can help users make the right decision when choosing a Wi-Fiprovider that suits their needs. Thus, this article not only provides a betterunderstanding of current Wi-Fi services, but also provides practical guidance forusers to choose a provider that suits their preferences and budget.